Knowledge and attitude towards computer usage among health care students in India -across sectional study - A Anitha; V Siva kalyan; M Pavana Sandya; T Madhavi Padma; KVNR Pratap (Wolters Kluwer Medknow Publications, 2013)
Background: As computers and internet usage is increasing rapidly in all fields more so with health care systems, an immediate attention on the computer knowledge and its application is needed for health professionals. Aim: To assess the knowledge of computer technology and their attitude towards its usage among health care students in an institution located in India. Materials & Method: A cross-sectional questionnaire based survey was conducted among dental, medical House surgeons (interns) and final year nursing students of Mamata Institutions in Khammam, Andhra Pradesh, India. A pretested closed ended questionnaire was prepared and was distributed. Results: A total of 260 subjects had participated in the study (female=170, male=90). About 42% of the subjects had their own computer or laptop; 84% of the students thought that a separate subject of computers should be added to the curriculum and 87% of the students thought that computers were necessary to manage patients' information. Conclusions: There is a need to improve the health care students' knowledge on computer education and application of this knowledge in to their clinical practice.